2020
DOI: 10.1111/hepr.13560
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of portopulmonary hypertension in cirrhotic patients who underwent both hepatic vein and pulmonary artery catheterization

Abstract: Portopulmonary hypertension (PoPH) is a well-known complication of liver cirrhosis. The aim of this study was to clarify the pulmonary hemodynamics and the prevalence and characteristics of PoPH in patients with portal hypertension. Methods: The subjects were 335 patients with portal hypertension diagnosed by hepatic vein pressure gradient (HVPG). Among them, 186 patients received measurements of pulmonary artery pressure (PAP), pulmonary artery wedge pressure (PAWP) and pulmonary vascular resistance (PVR). Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 42 publications
7
36
0
Order By: Relevance
“…Our study found that there were no differences in liver function, Child-Pugh classification, MELD score, or etiology between the POPH group and the non-POPH group. This is consistent with the results of a previous study that the Child-Pugh classification is not related to POPH [ 18 ]. Studies have shown that increased MELD scores in POPH patients before transplantation are associated with poor survival after transplantation [ 19 ], and we need to confirm this conclusion with long-term follow-up observation.…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that there were no differences in liver function, Child-Pugh classification, MELD score, or etiology between the POPH group and the non-POPH group. This is consistent with the results of a previous study that the Child-Pugh classification is not related to POPH [ 18 ]. Studies have shown that increased MELD scores in POPH patients before transplantation are associated with poor survival after transplantation [ 19 ], and we need to confirm this conclusion with long-term follow-up observation.…”
Section: Discussionsupporting
confidence: 93%
“…Portopulmonary hypertension (PoPH) is a severe complication of CLD. 35,36 PoPH is also a devastating complication of portal hypertension. 37,38 PoPH has a very poor prognosis; therefore, useful noninvasive tests for PoPH are needed.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] Concerning higher IVC-SD, it is generally recommended to esti- With regards to presence of PSSs, some studies showed a strong association between the development of spontaneous PSSs and onset of PoPH as in our results, 32,33 yet others did not find a correlation. 25 However, recently increased levels of vasoconstrictors such as serotonin and endothelin-1, produced in the splanchnic circulation, not metabolized by the liver, and reaching the pulmonary circulation via PSSs have been proposed as the mechanism responsible for the development of PoPH in cirrhosis. 6,34 In addition, PAP is increased as a result of increased pulmonary blood flow through PSSs as well as increased vasoactive substance-mediated pulmonary vascular resistance.…”
Section: Case Presentation Of Poph Diagnosed By Rhcmentioning
confidence: 99%